Materiality Conditions in the Interplay between Environment and Financial Performance: A Graphical Modeling Approach for EEA Oil and Gas Companies - Mirela Sichigea; Marian Siminica; Mirela Cristea; Gratiela Georgiana Noja; Daniel Circiumaru (Complexity)
The recovery after the unprecedented pandemic crisis that Europe has currently been facing is strengthening the strong dependence between social, economic, and environmental fields, maintaining green investments and innovation at the core of the European strategies. Shifting to clean industries is a challenging mission that a complex network of stakeholders and their different interests must take into account. Within this network, the interplay between environmental and financial performance of a company represents a common point with a growing emphasis on the transparency and the materiality capacity of the disclosed information. This paper uses the Structural Equation Modeling and the Gaussian Graphical Models as graphical analysis approaches and offers a first insight about the interaction between environmental materiality measures and financial performance. A preliminary step of the scientific research consisted of a hand-mapping investigation about materiality conditions. Starting from the Materiality Map developed by the Sustainability Accounting Standards Board (SASB), this paper extends the main concept about materiality and investigates it on three different content ranges, which focus on the general environmental policy of the company, the targets set, and its concrete footprint. The methodology approaches were grounded on a newly compiled dataset provided by the Thomson Reuters database for 194 Economic European Area (EEA) oil and gas companies. The results provide significant evidences for the manifestation of materiality and emphasize the informational content of the individual environmental measures as an important condition for its financial impact. Adding to the environmental-financial performance relationship, our findings have both practical and academic relevance for the economic field and sustainable growth goals.